Análise do processo de gerenciamento de resíduos sólidos no município de Francisco Beltrão/PR a partir da década de 1970 - Rigo, Vilmar (2014)
This master's thesis focuses the solid waste´s management in Francisco Beltrão county, starting from the decade of 1970, seeking to raise at first historical facts of how was the evolution in the generation and disposal of solid waste. The study shows how it was carried out and the main points of dumping of waste collected within the city limits, taking these points in the proximity to water resources and the environmental risks offered. It is noteworthy in this regard that the municipal administrations historically not showed a significant concern with environmental issues, since the forms of provisions of the waste collected would affect directly the natural resources, contaminating and compromising the local fauna and flora, and offering health risks of the population, especially with the emergence of vectors that cause diseases and pollution of water resources. In summary, the present study sought to raise information of the evolution in the management of solid waste, aiming to evaluate the participation of the municipal public power and the fulfilment of laws aimed at the National Policy of Solid Waste (PNRS), Federal Law no. 12,305, of august 02, 2010. For that study literature searches, queries to documents and interviews with State Prosecutor, Environmental Institute of Paraná (IAP), former employees of the municipal government of Francisco Beltrão were used, in addition to site visits at various points the municipality. As a result, the management of solid waste in the county presents a very positive development mainly from the year 2001, highlighting this year the construction of the landfill, the implementation of selective collection in 2006, and from 2010 the creation of echo points, the expansion of selective collection in urban and rural area and the development of the Integrated Solid Waste Plan of the municipality. Also points out the deficiencies still exist, and suggests some alternatives to suit them.